Computed Tomography Angiography Evaluation of Peripheral Arterial Disease and Correlation with Colour Doppler - M. Balaji Vara Prasad; Srinadh Boppana; Mounika Reddy; Nainika Juvvadi; Rajeshwari; Radhika (Asian Journal of Medical Radiological Research, 2020)
Background: Peripheral Arterial Disease Is a Major Problem Among the Population of Those 55 Years and Older. MDCT is a Non-Invasive Method of Visualization of Vascular System. It Affords More Widespread Vascular Screening, Allowing Diagnosis to be Made at an Early Stage. The objective is to Assess the Role of Multidetector Computed Tomography Angiography in Peripheral Arterial Disease of Lower Extremities. Subjects & Methods: A Prospective Study of 35 Patients with Signs and Symptoms of PVD, Were Subjected to Colour Doppler Ultrasonography and MDCT Examination Between a Period of 1st August 2018 to 31st May 2019. Results: Our Study Shows a Very Good Sensitivity, Specificity, PPV, NPV and Accuracy of Doppler in Assessing the Soft Plaque (82%, 100%, 100%, 97%, 97% Respectively) & in Evaluation of Stenosis Like <50% Stenosis (100%, 99%, 85%, 100% & 99% Respectively), 50-99% Stenosis (100%, 99%, 96%. 100% & 99.8% Respectively), & Occlusion (84%, 100%. 100%, 98% & 98% Respectively). The Only Parameter Which Showed Poor Result Was in Evaluation of Calcified Plaque. Conclusion: Our Study Shows that Both Colour Doppler & MDCT Can Be Complimentary in Lower Limb Arterial Disease Evaluation.